Family resilience: report of a research with female same-sex couples with children - Paula Machado; Elaine Rabinovich (Millenium)
Introduction: Homosexuals have been transforming the family institution by making efforts to get their right to marry and have children recognized. Studies in Brazil on homoparenting are few in number and recent, and there is a need to understand the processes that promote resilience in homosexual families, given that these families have to deal with stigma and discrimination.